ASSESSMENT OF NUMBER AND LEVEL OF ATTACHMENT OF BUCCAL FRENUM IN THE EDENTULOUS OLD AGE PEOPLE IN A TERTIARY CARE CENTER OF NEPAL - Mishra Sapkota, Srijana; Narayan Thakur, Smriti; Chaulagain, Rajib (Journal of Chitwan Medical College, 2024)
Background: Frenum is a fold of mucous membrane that encase muscle fibers. Frenum are important anatomical structure during complete denture fabrication. There is paucity of data related to buccal frenum. This study aimed to assess the number and level of buccal frenal attachment among the edentulous age groups and genders in both the maxillary and mandibular arches. Methods: A descriptive cross-sectional study was conducted in the Department of Prosthodontics & Maxillofacial Prosthetics of Chitwan Medical College. In total 97 patients of within the age of 55-85 years’ old participated in the study. In this study demographic details of participants followed by level and number of buccal mucosa in the oral cavity were noted in a predesigned proforma. The collected data was then transferred into SPSS and was analyzed for descriptive statistics using SPSS version 26. Results: In this study, in total 97 complete edentulous patients participated in which 59 (60.8%) were males and rest were females. Single buccal frenum was mostly observed in the maxillary arch. About 49(50.5%) of the participants showed single buccal frenum on right side of maxillary arch, while on the left side 40 (41.2%) of the participants had single buccal frenum. In the mandibular arch, 62 (63.9 %) on the right side and 68 (70.1%) on the left side had no frenum at all. Conclusions: From this study it can be concluded that there is variation in the buccal frenum too. In order to provide proper retention, stability, and support with the least amount of post-placement corrections, a solid understanding of the morphological variation of frenum is thus necessary.